Giới thiệu địa chất thủy văn môi trường - Học, Bùi; Hoàng, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2005)
Environmental issues have been recognized as urgent problems for developed countries and developing countries as well due to the global economy. To meet the needs of this new study field in most of economic and scientific branches had been formed in order to minimize the negative environmental effects. It can be state that geological science plays an important role in this new development trend: environmental issues have been addressed in almost all geological activities, including hydrogeology. The environmental issues in hydrogeology can be listed as optimal groundwater abstraction, groundwater quality and contamination, sea water intrusion into groundwater, land subsidence due to groundwater abstraction etc. This paper has intention to discuss and get comments on the name of this environmental hydrogeology, its objectives and contents.